Analisis Kemampuan Multiple Representasi Siswa Kelas XI MAN 1 Pekanbaru Pada Materi Titrasi Asam Basa - Mainur Hikmayanti; Lisa Utami (LPPM Universitas Negeri Jakarta, 2019)
This research was instigated that the understanding of chemistry needed thinking ability using three different interrelated representation levels—macroscopic, submicroscopic, and symbolic. This research aimed at knowing how student multiple representation ability at the eleventh grade of State Islamic Senior High School 1 Pekanbaru on Acid-Base Titration lesson was. Quantitative Descriptive method was used in this research. The samples were eleventh-grade students of MIA 2, and they were 30 persons selected by using Purposive sampling technique. The instruments of collecting the data were multiple representation tests that were in the forms of multiple-choice question and essay and interview. Based on the data analysis, it was obtained that the mean score of student multiple representation ability was 95.33% at the macroscopic level, 64.58% at the symbolic level, and 41.11% at the submicroscopic level. Research findings showed that the mean of student multiple representation ability achievements on the aspect of cognitive knowledge was 67.00%, the achievement was on good category and it indicated that the knowledge aspect mastery of student multiple representation ability on Acid-Base Titration was on good category. Keywords Multiple Representation, Acid-Base Titration